Application for Second Marriage Dispensation And its Relevance to Child Protection (Study In The Jurisdiction Of Wonosobo Religious Court) (Pandecta Research Law Journal, 2022)
This study aims to find out why there is still a request for a second dispensation and how the second marriage dispensation is implemented in terms of the principle of child protection. This research is an example of empirical juridical research, which is research done in the field by looking at the laws that are in place and how they are used in people’s lives. The study’s results show that different ways of interpreting the rules in Article 7 paragraph 1 of Law 16/2019 have led to several KUA in Wonosobo still requiring prospective brides under the age of 19 to submit a second marriage dispensation, even though they are already widowed or widowers. According to the rules, a dispensation for marriage only needs to be filed once. This is because a person is considered legally competent after getting married. On the other hand, when considering the principle of child protection, filing for a second dispensation for marriage is required. This study was made so that the Religious Courts and KUA, as well as anyone else who was interested, could use it as a guide to understand how important it is to have the same ideas about applying for a second marriage dispensation.